The Influence Of Work Environment, Organizational Culture, And Involvement On Performance With Lean Manufacturing As A Mediating Variable In Tjiwi Kimia Tbk Paper Mill Employees. - Radittya Mahasputra Antara; Agung Winarno; Sopiah (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the influence of the work environment, organizational culture, and employee engagement on employee performance with Lean Manufacturing as a mediating variable. The research population amounted to 255 employees consisting of various levels of positions, with a sample of 154 respondents selected using proportional sampling techniques in 4 sections/divisions. Data collection was carried out through a questionnaire with a Likert scale and analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results of the study show that the work environment, organizational culture and employee involvement have a positive and significant effect on the implementation of Lean Manufacturing. Lean Manufacturing, work environment, and organizational culture have a positive and significant effect on employee performance, employee involvement does not have a significant effect directly on employee performance. Meanwhile, the indirect influence of the work environment, organizational culture, and employee involvement has a positive and significant effect on employee performance through the mediation of Lean Manufacturing implementation. An important finding of this study is that Lean Manufacturing acts as a full mediator between employee engagement and employee performance. This research provides a theoretical contribution in integrating Socio-Technical Systems Theory (STS) and Social Exchange Theory (SET) in the context of the manufacturing industry in Indonesia, as well as providing practical implications for companies to integrate human factor management with Lean systems synergistically to improve organizational performance in a sustainable manner.